2021
DOI: 10.5194/hess-2021-71
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of long-term spatiotemporal variations in regional-scale groundwater recharge: Contributions of a water budget approach in southern Quebec

Abstract: Abstract. Groundwater recharge (GWR) is recognized to be a strategic hydrologic variable, necessary to estimate when implementing sustainable groundwater management, especially within a global change context. However, its simulation at the regional scale and for long-term conditions is challenging, especially due to the limited availability of spatially-distributed calibration data and to the rather short observed time series. The use of a superficial water budget model to estimate recharge is appropriate for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…The overall annual variability in PGR over time is linked to that of temperature and VI. Here, the observed relationships between PGR, VI and temperature patterns are consistent with that reported in other studies undertaken under similar climate conditions and comparable geological environments (Chemingui et al, 2015; Dubois et al, 2021; Hayashi & Farrow, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The overall annual variability in PGR over time is linked to that of temperature and VI. Here, the observed relationships between PGR, VI and temperature patterns are consistent with that reported in other studies undertaken under similar climate conditions and comparable geological environments (Chemingui et al, 2015; Dubois et al, 2021; Hayashi & Farrow, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The annual increase in PGR simulated in this study for the consistent with the results from the PGR study conducted by Dubois et al (2021) in the Montreal region of Southern Quebec. In this comparable study, Dubois et al (2021) found that PGR presented a statistically significant increasing trend over 56 years (1961–2017). In this study, O.P.#4 shows a steep increase in PGR rates, whereas O.P.#1 shows the most modest increase in PGR rates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Under a wide variety of conditions, GR is still considered to be one of the most challenging water-balance components to quantify (Dripps and Bradbury 2007) because it is difficult to measure directly and it is strongly influenced by climate, soil heterogeneity and land use. A wide range of methods (Scanlon et al 2002) has been shown to be useful in assessing the quantity of water actually replenishing an aquifer, including isotopic profiles (Barbecot et al 2018;Mattei et al 2020a, b), remote sensing techniques (Jackson 2002), chloride mass balance (Szilagyi et al 2011), base flow separation (Hung Vu and Merkel 2019), unsaturated zone modeling (Hu et al 2019;Mattei et al 2020a), water balance models (Dubois et al 2021) and water table fluctuations (Crosbie et al 2005). The reliability of these methods depends on a variety of factors, including the availability of field data to describe site characteristics, such as soil type, vegetation and depth to the water table (Scanlon et al 2002).…”
Section: Introductionmentioning
confidence: 99%